CRITERION ANTIWEAR CHARACTERISTICS OF LUBRICATION OILS - V.T. KOSTYGOV (Advanced Engineering Research)
It was suggested a new conception of identification of wear intensity of lubricated steel friction surfaces by size and distribut6ion of micromechanical characteristics in thin undersurface level, deformated by friction. Suggested criterion characterize antiwear features of lubrication oils.